Informalidade no mercado de trabalho: uma análise qualitativa com foco nos trabalhadores por conta própria - Almeida, Gustavo Garcia Vieira de (2015)
The Brazilian labor market is known for its high informality rates. Therefore, governments have sought to implement actions to reduce these rates. The National Statute of Micro and Small Businesses, implemented by the Simples Nacional, can be seen as a major attempts to solve this challenge. The Statute created the figure of the Microempreendedor Individual, reducing costs and providing benefits for its formalization. This study aimes to investigate the main motivations involved in informality and choice of self-employed to formalize. Thus, this paper discusses the concepts of informality, estimated its size in the Brazilian economy and review its causes and consequences. The search also presents the government incentives for small businesses formalization, with main focus to Microempreendedor Individual This category is investigated, identifying the gains brought to the Brazilian labor market and the main challenges that remain. From a qualitative analysis using questionnaires with self employed workers, it presents understand discussion aboutthe causes of the current membership of the MEI and additionally seek the opinion of the interviewees about the Brazilian institutions and what they still need to move forward.